PENGARUH KEPEMIMPINAN KEPUASAN KERJA TERHADAP KINERJA Studi Korelasional Pada Pegawai Dinas Ciptakarya Kabupaten Lebak - Yumhi . (E-Journal Studia Manajemen, 2013)
This reserch is aimed at evaluate the efect of leadershipstyle , Job Satisfaction to job performance with methodology correlational survey at sixty eaght responden in Dinas Ciptakarya Kabupaten Lebak. The result that leadershipstyle influnces to job performance, job satisfaction influnces to job performance and simultanouses influnce between leadership style and job satisfaction to job performance. Therefore the conclusion is leadership style and job satisfacton are factors that contrubutes increasing job performance